Multiple effects of β-amyloid on single excitatory synaptic connections in the PFC - Wang, Yun; Zhou, Thomas H.; Zhi, Zhina; Barakat, Amey; Hlatky, Lynn; Querfurth, Henry (Frontiers in Cellular Neuroscience, 2013)
Prefrontal cortex (PFC) is recognized as an AD-vulnerable region responsible for defects in cognitive functioning. Pyramidal cell (PC) connections are typically facilitating (F) or depressing (D) in PFC. Excitatory post-synaptic potentials (EPSPs) were recorded using patch-clamp from single connections in PFC slices of rats and ferrets in the presence of Aβ. Synaptic transmission was significantly enhanced or reduced depending on their intrinsic type (facilitating or depressing), A species (A40 or A42) and concentration (1-200 nM vs. 0.3 - 1M). Nanomolar Aβ40 and Aβ42 had opposite effects on F-connections, resulting in fewer or increased EPSP failure rates, strengthening or weakening EPSPs and enhancing or inhibiting short-term potentiation (STP: SA and PTP), respectively. High Aβ40 concentrations induced inhibition regardless of synaptic type. D-connections were inhibited regardless of Aβ species or concentration. The inhibition induced with bath application was hard to recover by washout, but a complete recovery was obtained with brief local application and prompt washout. Our data suggests that Aβ40 modulates facilitation and depression of synaptic activity. At higher levels, Aβ40 and Aβ42 may induce inhibition only, further irreversible toxicity once diffusely accumulated in the synaptic environment.